Protein Corona Attenuates the Targeting of Antitumor Sialyl Lewis X-Decorated Liposomes to Vascular Endothelial Cells under Flow Conditions - Natalia R. Onishchenko; Alexey A. Moskovtsev; Maria K. Kobanenko; Daria S. Tretiakova; Anna S. Alekseeva; Dmitry V. Kolesov; Anna A. Mikryukova; Ivan A. Boldyrev; Marina R. Kapkaeva; Olga N. Shcheglovitova; Nicolai V. Bovin; Aslan A. Kubatiev; et al. (MDPI AG, 2023)
Previously, we showed in the human umbilical vein endothelial cells (HUVECs) model that a liposome formulation of melphalan lipophilic prodrug (MlphDG) decorated with selectin ligand tetrasaccharide Sialyl Lewis X (SiaLeX) undergoes specific uptake by activated cells and in an in vivo tumor model causes a severe antivascular effect. Here, we cultured HUVECs in a microfluidic chip and then applied the liposome formulations to study their interactions with the cells in situ under hydrodynamic conditions close to capillary blood flow using confocal fluorescent microscopy. The incorporation of 5 to 10% SiaLeX conjugate in the bilayer of MlphDG liposomes increased their consumption exclusively by activated endotheliocytes. The increase of serum concentration from 20 to 100% in the flow resulted in lower liposome uptake by the cells. To elucidate the possible roles of plasma proteins in the liposome-cell interactions, liposome protein coronas were isolated and analyzed by shotgun proteomics and immunoblotting of selected proteins. Proteomic analysis showed that a gradual increase in SiaLeX content correlated with the overall enrichment of the liposome-associated proteins with several apolipoproteins, including the most positively charged one, ApoC1, and serum amyloid A4, associated with inflammation, on the one hand, and a decrease in the content of bound immunoglobulins, on the other. The article discusses the potential interference of the proteins in the binding of liposomes to selectins of endothelial cells.